THE CONSTRUCTION OF STUDENTS’ DIGITAL MORAL INTELLIGENCE THROUGH ISLAMIC RELIGIOUS EDUCATION - Hani Nafi'ah Rachmawati Hani; Iffatul Afifah Afifah; Lyke Nuroniyah Lailatul Lutfhi Lyke; Benny Prasetiya Benny (TARBIYAH DARUSSALAM: JURNAL ILMIAH KEPENDIDIKAN DAN KEAGAMAAN, 2026)
This study discusses the construction of students’ digital moral intelligence through Islamic Religious Education as a response to moral problems in digital spaces. The digital era provides easier access to information, but it also gives rise to issues such as hoaxes, cyberbullying, hate speech, plagiarism, weak communication ethics, and a lack of responsibility for digital footprints. The purpose of this study is to formulate the construction of students’ digital moral intelligence based on the values of Islamic Religious Education from the perspective of Al-Ghazali’s concept of akhlak. This study employs a library research method by examining books, journal articles, proceedings, academic documents, and other relevant scientific sources. The data are analyzed using a descriptive-qualitative approach through reading, note-taking, classifying, comparing, and synthesizing various concepts. The findings show that digital moral intelligence is an extension of the concept of akhlak in digital life, which can be developed through the values of tabayun, amanah, honesty, adab, ihsan, and responsibility. This construction includes cognitive, affective, and practical dimensions. This study concludes that Islamic Religious Education plays a strategic role in shaping students who are religious, critical, polite, and responsible in digital life.